Stressful Events in Old Age: Who are Most Exposed and Who are Most Likely to Overcome Them - Herrera, M. Soledad (Gerontol Geriatr Med, 2020)
Objectives: This study investigated self-reported events that were rated as stressful and being affecting wellbeing among older people. It also examined the variables associated with the perception of overcoming these stressful events. Methods: Face-to-face survey on a representative sample of 1,431 older people in Santiago-Chile. Instruments included open-ended questions for distinguishing events as losses, problems, conflicts, and others’ difficulties. The associations between the occurrence and overcoming of events with individual and social characteristics were examined through multivariate logistic regression. Results: 39.5% mentioned at least one stressful event, being mostly perceived as solvable problems rather than losses. Higher-income, better health, self-efficacy, and social support were associated with a higher perception of event overcoming. Conclusion: The occurrence and the probability of events’ overcoming does not increase in old-old age in this sample group. Better health and individual and social resources such as self-efficacy and social support, are protective resources for overcoming the stressful events, but they are not generally considered in public policies.